(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
Multiple interpretations have been given to the signature of the Cerveteri crater painter (VII century B.C.). The first, and most likely one, is that provided by Wilamowitz, according to whom the name would be composed of aristos and nothos “illegitimate son”. Considering on the other hand the shape of the letters and the linguistic peculiarity of the verb (epoiésen), it is possible to deduce the origin of the product from an Italic area where Ionic dialect was spoken, probably an Euboean colony (Boardman).